Análise da transferência de tecnologia externa orientada à indústria 4.0: vínculos colaborativos entre fornecedor e indústria de manufatura - Silva, Vander Luiz da (2019)
In the Industry 4.0, basically, Technologies are designed to make production processes more flexible, accurate, reliable and advanced and assist in organizational management. For an industry which aims to apply the Industry 4.0 concepts in its organizational and productive environments, the Technology Transfer (TT) process will be required. The focus of this study is on the external TT (management of technologies originating from organizations outside the applicant industry). The aim of this study is to analyze the technical specificities (barriers and phases) of TT between suppliers and industry, in the Industrial 4.0 Scenario. The method of approach used was qualitative. The research is of a descriptive, exploratory and bibliographic nature. A literature review was elaborated using structured protocols and criteria to select the scientific material. Five research axes were established (Research axes 1 and 2 aims to obtain studies to understand the area of TT; 3 for understanding the Industry 4.0 in general; and 4 and 5 for TT discussions in the Industry 4.0). Through this review, the theoretical approach was enriched and a TT model was proposed. The barriers to TT in the Industry 4.0 were identified and a TT model consisting of ten phases was proposed and characterized. This study provides useful information to industries interested in Industry 4.0 practices. Can assist small, medium and large companies in the transfer of conventional technologies, because the proposed phases are theoretical. The scope of the TT has been expanded. For future research, more in-depth studies on integrated TT to Industry 4.0 approaches are suggested.